Long-term Imatinib Treatment does not Cause Testicular Toxicity in Male Adolescents with Chronic Myeloid Leukemia and in a Juvenile Rat Model - Tauer, J. T.; Ulmer, A.; Glauche, I.; Jung, R.; Suttorp, M. (Klinische Pädiatrie, 2014)
Background: The impact of exposure to the tyrosine kinase inhibitor (TKI) imatinib (IMA) on the male reproductive endocrine system is still discussed controversially. We therefore investigated testosterone (Testo) and inhibin B (InB) in blood serum from male adolescents with chronic myeloid leukemia (CML) under long-term TKI treatment. Also long-term exposure to TKIs was studied in a juvenile rat model.Methods: Serum was collected at 3 months intervals from 13 boys (age: 7.8–18.9 years, median: 12.8 years) with CML receiving TKI treatment over 3–58 months (median: 18 months). 4 weeks (w) old male rats were exposed, either chronically or intermittently, via the drinking water to a standard (SD) and a high dose (=2-fold SD) of IMA, dasatinib (DASA), or bosutinib (BOSU) over a 10 w period. Controls received water only. Animals were sacrificed after 2 w (prepubertal), 4 w (pubertal), and 10 w (postpubertal) of exposure. Testo and InB serum levels were measured by ELISA.Results: Boys exhibited Testo and InB levels within normal age-related reference ranges and no pattern of rising or falling levels during TKI treatment could be observed. In rats, Testo levels under IMA exposure tended to be non-significantly lowered at postpubertal age compared to controls while no significant differences were found under DASA and BOSU exposure. Animals’ InB levels did not significantly differ from controls for all TKIs, at all doses, and by all application schemes tested.Conclusion: With the limitation that the number of individuals tested was rather small, testicular toxicity due to TKI seems unlikely as no alterations of Testo and InB blood levels neither in male adolescent patients nor in rats under long-term TKI exposure was observed.
Keywords: CML; imatinib; boys; fertility; rat model